ANALYSIS OF THE DIFFICULTIES OF CONSTITUTIONAL LAW STUDENTS IN LEARNING ENGLISH TENSES AT THE AL-ZAYTUN INSTITUTE - Zaelani, Ahmad; Hanif Al-Gifari, Muhsin; Ramdhani, Ahmad; Rifqi Alkamil, Fathir; Rahmadona, Anisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Tenses in English are used to convey when an event occurs or someone does something. Tenses are divided into 4 types namely present, past, future, and fast future. Tenses material provides specific guidance in making effective sentences and expressing activities in the past, present, and future. This research aims to analyze students' difficulties in learning English tenses. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews and participant observation of students of constitutional law at Al-Zaytun Islamic Institute of Indonesia, in learning English tenses. The results showed that 90% of constitutional law students in the Midterm Examination on average only knew 5 tenses out of 13 tenses. This research shows that most students of constitutional law do not have a strong basic understanding of the structure and basic concepts of English grammar, especially tenses. This is due to the lack of emphasis on grammar as well as student interest. Keywords: Tenses, Students, Al-Zaytun